(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article analyzes modern and resource-efficient approaches to processing organic secondary raw materials for the production of synthetic fuels. Organic secondary raw materials include agricultural residues, food waste, sewage sludge, wood-processing residues, livestock waste and the biodegradable fraction of municipal and industrial waste. These resources are traditionally treated as low-value waste, but under conditions of energy transition and circular economy they can become an important feedstock for producing syngas, bio-oil, biomethane, hydrogen, renewable methanol and synthetic liquid hydrocarbons.